The Potency and Urgency of Implementing Green Education in Sumenep Madura - Helliyatul Matlubah; Herowati; Sindi Arista Rahman; Rizal Andi Sya'bana (Postgraduate, University of Mataram, 2025)
The environmental problems in Sumenep are concerning since the establishment of the Suramadu Bridge. These problems include the expansion of the extractive industry in Sumenep causing natural resource assets to shift ownership as well as threats from the mining sector which is causing an environmental crisis. The education sector should be at the forefront of educating the younger generation to face these environmental problems. One of the efforts in the education sector is through the implementation of green education in Sumenep in both formal and non-formal institutions. More comprehensive research regarding the importance of green education, especially in the Sumenep area, is necessary. This research aims to examine how formal and non-formal schools organize their learning starting from systems, curriculum, teaching materials and methods in relation to environmental issues. This research employed a descriptive-qualitative approach with a case-study design at three schools in Sumenep, namely MAN Sumenep, SMA 3 Annuqayah and KKAA-Nature School Community. The data collection methods included the questionnaire and interview. The findings show that the three-types of schools implemented green education with various systems, curricula, teaching materials and methods.